Programmes of Industrial Development 1956-61 (Metallurgical Industries) - Planning Commission (Planning Commission, 1959)
When the First Five Year Plan was published towards the end of 1952, there was brought out at the same time a volume entitled “Programmes of Industrial Development, 1951-56” containing studies of 42 organised industries. In the present volume, there are gathered together statistical data relating to 51 organised industries together with programmes for their expansion during the period, of the Second Five Year Plan. All the industries covered by the previous volume have again been included and the following have been added : (1) Structural fabrication (2) Industrial machinery (3) Ferro-manganese (4) Coal carbonisation (5) Dyestuffs and intermediates (6) Refractories (7) Rubber manufactures (8) Coated abrasives (9) Plastics (10) Starch and glucose (11) Biscuits and confectionery and (12) Fruit and vegetable preservation. Textile machinery and machine tools treated separately in the earlier volume are dealt with under Industrial machinery, and Grinding wheels and Coated abrasives are treated together so that the number of organised industries in this volume comes to 51.
Government of India Planning Commission